Another way of solving the problem (cos x)² - (sin x)² = 2(cos x)² - 1

is as follows:

Consider the right-hand side (RHS) of the equation: 2(cos x)² - 1

From the Pythagorean Identity, we know that (cos x)² + (sin x)² = 1

Thus substitute 1 with (cos x)² + (sin x)² in the RHS of the equation:

2 (cos x)² - ((sin x)² + (cos x)² ).

Expand to give 2(cos x)² - (sin x)² - (cos x)² = (cos x)² - (sin x)² (as given by the LHS of the original equation).

Thus (cos x)² - (sin x)² = 2 (cos x)² - 1

Alternatively, we can start with the right-hand side and show that it equals the left hand side.

Rewrite the right hand side, 2(cosx)² - 1, as (cos*x*)² + (cos*x*)² - 1, which can also be rewritten as

(cos*x*)² - (1 - (cos*x*)²) by switching the order of the second and third terms and factoring out negative sign.

Then, according to Pythagorean Identity, (sin*x*)² + (cos*x*)² = 1, the expression in the parenthesis, 1 - (cos*x*)², can be replaced by (sin*x*)²:

(cos*x*)² - (1 - (cos*x*)²) = (cos*x*)² - (sin*x*)².

**This, we have shown that (cos x)²**

**- (sin**

*x*)²**= 2(cosx)²**

**- 1.**

We have to prove that: (cos x)^2 - (sin x)^2 = 2*(cos x)^2 - 1

Starting with the left hand side:

We use the relation (cos x)^2 + (sin x)^2 = 1 or (sin x)^2 = 1 - (cos x)^2

=> (cos x)^2 - (sin x)^2

=> (cos x)^2 - (1 - (cos x)^2)

=> (cos x)^2 - 1 + (cos x)^2)

=> 2(cos x)^2 - 1

which is the right hand side.

**Therefore we prove that (cos x)^2 - (sin x)^2 = 2*(cos x)^2 - 1**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.